2020
DOI: 10.1093/cid/ciaa1433
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome Sequencing to Track Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Transmission in Nosocomial Outbreaks

Abstract: Background During the first wave of the coronavirus disease 2019 (COVID-19) pandemic, outbreaks of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in healthcare institutions posed a significant problem. Due to limited evidence, guidance on appropriate infection prevention and control (IPC) measures such as the wearing of face masks varied. Here, we applied whole virus genome sequencing (WvGS) to analyse transmission routes of SARS-CoV-2 in hospital-acquired (HA) COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
140
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(158 citation statements)
references
References 21 publications
8
140
0
1
Order By: Relevance
“…The risk among HCWs has been the subject of several studies [ [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. In February 2020, the Chinese Center for Disease Control and Prevention published a major report on more than 72,000 cases of COVID-19 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk among HCWs has been the subject of several studies [ [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. In February 2020, the Chinese Center for Disease Control and Prevention published a major report on more than 72,000 cases of COVID-19 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adapted and correctly applied prevention measures reduce the nosocomial risk for HCWs, as shown by a study of the seroprevalence in medical staff several weeks after taking care of COVID-19 patients [ 27 ]. However, proven nosocomial infections occurred during loosening of barrier measures between HCWs, [ 28 ] lead outbreaks that can reached high attack rates [ 29 ]. In March 2020, Belingheri et al.…”
Section: Discussionmentioning
confidence: 99%
“…Most countries struggled with insufficient testing capacity in the first months of the pandemic, which hampered early detection of emerging outbreaks and implementation of infection control measures. Increasing experience now suggests that every suspected healthcare associated infection should trigger a bundle of immediate infection control measures, including extensive screening for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), quarantining of all patients on the affected ward, physical distancing between personnel, and use of reinforced PPE during all contact with patients on the affected ward, in order to prevent larger outbreaks 101112…”
mentioning
confidence: 99%
“…Working in intensive care units is not associated with an increased risk of infection, possibly owing to the protection afforded by high level PPE or to the decrease in infectivity that occurs in the later stages of the illness, even among critically ill patients 1315. The greatest risk to healthcare workers may be their own colleagues or patients in the early stages of unsuspected infections when viral loads are high 12…”
mentioning
confidence: 99%
“…Previous studies have shown high nosocomial transmission rates of SARS-CoV-2 between HCWs and/or patients [ 15 ]. However, our sequencing results suggest that infection of HCWs occurred in their respective communities, outside of the clinic and was not nosocomial.…”
Section: Discussionmentioning
confidence: 99%